The Role of Product-influencer Congruence, Influencer credibility, and Attitude toward Advertising on Purchase Intention - Putri, Nadia Ramadhani Nugroho; Handriana, Tanti (Southeast Asian Business Review, 2023)
The aims of this study to see whether there is an effect of product-influencer congruence on influencer credibility and attitude toward advertising and how it impacts purchase intention. This study examines the suitability of Avoskin Your Skin Bae Shield of Sun Essence products and influencer Refal Hady who is the star of advertisements that uploaded via Instagram reels. Using a quantitative approach, this research examines data through SEM (Structural Equation Modeling) analysis techniques based on Partial Least Square (PLS) and uses the SmartPLS 3 application. Respondents in this study are Instagram users who have watched Avoskin Your Skin Bae Shield of Sun Essence advertisement. starring Refal Hady but have never bought the product, are over 18 years old and there are 175 respondents who have fulfilled the screening. The results of this study indicate that product-influencer congruence has a positive influence on influencer credibility and attitude toward advertising, and has an impact on purchase intention, and attitude toward advertising has a positive influence on purchase intention. However, influencer credibility has no influence on purchase intention.